(untitled) (Homiletic, 2013)
Based on new empirical studies this essay explores how churchgoers listen to sermons in regard to the theological notion that “faith comes from hearing.” Through Bakhtinian theories presented by Lorensen and empirical findings presented by Gaarden, the apparently masked agency in preaching that infuses faith can be described as a polyphony of voices, which is not limited to the liturgical room or the sermon, but is activated by it. This polyphony creates a room, where the churchgoers, through different kinds of dialogical interaction (categorized as associative, critical, and contemplative) create new meaning and understanding. It is not a room that the listener or the preacher can control or occupy, but a room in which both engage.